MicroRNAs in Podocyte Injury in Diabetic Nephropathy - Ishii, Hiroki; Kaneko, Shohei; Yanai, Katsunori; Aomatsu, Akinori; Hirai, Keiji; Ookawara, Susumu; Ishibashi, Kenichi; Morishita, Yoshiyuki (Frontiers in Genetics, 2020)
Diabetic nephropathy is one of the major complications of diabetes mellitus and is the leading cause of end-stage renal disease worldwide. Podocyte injury contributes to the development of diabetic nephropathy. However, the molecules that regulate podocyte injury in diabetic nephropathy have not been fully clarified. MicroRNAs (miRNAs) are small noncoding RNAs that can inhibit the translation of target messenger RNAs. Previous reports have described alteration of the expression levels of many miRNAs in cultured podocyte cells stimulated with a high glucose concentration and podocytes in rodent models of diabetic nephropathy. The associations between podocyte injury and miRNA expression levels in blood, urine, and kidney in patients with diabetic nephropathy have also been reported. Moreover, modulation of the expression of several miRNAs has been shown to have protective effects against podocyte injury in diabetic nephropathy in cultured podocyte cells in vitro and in rodent models of diabetic nephropathy in vivo. Therefore, this review focuses on miRNAs in podocyte injury in diabetic nephropathy, with regard to their potential as biomarkers and miRNA modulation as a therapeutic option.